Adverse events of systemic immune-based combination therapies in the first-line treatment of patients with metastatic renal cell carcinoma: systematic review and network meta-analysis. Issue 4 (July 2021) - Quhal, Fahad; Mori, Keiichiro; Remzi, Mesut; Fajkovic, Harun; Shariat, Shahrokh F.; Schmidinger, Manuela
Abstract : Purpose of review: To compare the safety profiles of systemic immune checkpoint inhibitor-based combination therapies that were evaluated in the first-line setting of the management of patients with advanced or metastatic renal cell carcinoma (mRCC). Recent findings: Six phase III randomized control trials comparing first-line immune-based combination therapies to sunitinib in previously untreated patients with mRCC. Network meta-analyses were conducted to compare treatment-related adverse events (TRAEs), treatment discontinuation, and treatment-related mortality. Summary: Lenvatinib plus pembrolizumab was associated with the highest likelihood of grade ≥3 TRAEs, and treatment discontinuation rates. Nivolumab plus ipilimumab was associated with the lowest rates of grade ≥3 TRAEs. However, it was associated with a higher likelihood of endocrine-related adverse events (AEs). A higher likelihood of high-grade diarrhea was associated with pembrolizumab plus axitinib and avelumab plus axitinib. All combinations showed low rates of hematological AEs. Abstract : Supplemental Digital Content is available in the text